2012
DOI: 10.1364/josaa.29.002159
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Gaussian Schell-model beams

Abstract: In a recent publication [Opt. Lett.37, 2970 (2012)10.1364/OL.37.002970], a novel class of planar stochastic sources, generating far fields with flat intensity profiles, was introduced. In this paper we examine the behavior of the spectral density and the state of coherence of beamlike fields generated by such sources on propagation in free space and linear isotropic random media. In particular, we find that at sufficiently large distances from the source, the medium destroys the flat intensity profile, even if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(78 citation statements)
references
References 10 publications
3
74
0
Order By: Relevance
“…Partially coherent fields can cause several different kinds of modifications to the spatial intensity distribution, such as self-focusing and far-field flat topping, among many others [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, they are not the only extraordinary phenomena caused by partial coherence; some correlation functions can decrease scintillation in atmospheric turbulence [17], while others increase the resolving power of imaging systems [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Partially coherent fields can cause several different kinds of modifications to the spatial intensity distribution, such as self-focusing and far-field flat topping, among many others [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, they are not the only extraordinary phenomena caused by partial coherence; some correlation functions can decrease scintillation in atmospheric turbulence [17], while others increase the resolving power of imaging systems [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The far field generated by RGSM beam propagating in free space may have flat square/rectangular intensity distribution, which is different from the flat circular intensity distribution produced by the multiGaussian Schell model beams or the electromagnetic sinc Schellmodel beams [2][3][4][5]. The pattern of the RGSM beam throughout far field keeps invariant.…”
Section: Introductionmentioning
confidence: 93%
“…Multi-Gaussian correlated Schell-model (MGCSM) beam introduced in Ref. [12] displays far-field flat-topped beam profile although it has a Gaussian beam profile in the source plane [12,23] . Both theoretical and experimental results have demonstrated that an MGCSM beam exhibits lower scintillation than a GSM beam in turbulence [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%